Antimicrobial Potential and Chemical Characterization of Serbian Liverwort (Porella arboris-vitae): SEM and TEM Observations. (9th January 2013) - Kumar Tyagi, Amit; Bukvicki, Danka; Gottardi, Davide; Veljic, Milan; Guerzoni, Maria Elisabetta; Malik, Anushree; Marin, Petar D.
Abstract : The chemical composition of Porella arboris-vitae extracts was determined by solid phase microextraction, gas chromatography-mass spectrometry (SPME GC-MS), and 66 constituents were identified. The dominant compounds in methanol extract of P . arboris-vitae were β -caryophyllene (14.7%), α -gurjunene (10.9%), α -selinene (10.8%), β -elemene (5.6%), γ -muurolene (4.6%), and allo-aromadendrene (4.3%) and in ethanol extract, β -caryophyllene (11.8%), α -selinene (9.6%), α -gurjunene (9.4%), isopentyl alcohol (8.8%), 2-hexanol (3.7%), β -elemene (3.7%), allo-aromadendrene (3.7%), and γ -muurolene (3.3%) were the major components. In ethyl acetate extract of P . arboris-vitae, undecane (11.3%), β -caryophyllene (8.4%), dodecane (6.4%), α -gurjunene (6%), 2-methyldecane (5.1%), hemimellitene (4.9%), and D-limonene (3.9%) were major components. The antimicrobial activity of different P . arboris-vitae extracts was evaluated against selected food spoilage microorganisms using microbroth dilution method. The Minimal Inhibitory Concentration (MIC) varied from 0.5 to 1.5 mg/mL and 1.25 to 2 mg/mL for yeast and bacterial strains, respectively. Significant morphological and ultrastructural alterations due to the effect of methanolic and ethanolic P . arboris-vitae extracts on S . Enteritidis have also been observed by scanning electron microscope and transmission electron microscope, respectively. The results provide the evidence of antimicrobial potential of P . arboris-vitae extracts and suggest its potential as natural antimicrobial agents for food preservation.